Chatbots for Third-Party Monitoring : CivicTech Pilot in Madagascar - Rakotomalala, Olivia; Peixoto, Tiago; Kumagai, Saki (World Bank, Washington, DC, 2020)
Growing evidence confirms that citizen engagement is key to improving the delivery and quality of public services, management of public finances, and to promoting social inclusion, resulting in tangible improvements in people’s lives. The advent and availability of new technologies provide new opportunities to reach citizens, aggregate their ‘voice’ and demand, help governments respond, and partner with citizens to find and implement solutions collectively. With the right approach, CivicTech enables citizens to overcome income, social, and geographical barriers to interact with governments and participate at the local or national level. The CivicTech pilot in Madagascar supported the development of a Facebook ChatBot (bot) to enable third-party monitoring of service delivery operations for the Madagascar Public Sector Performance Project (PAPSP, P150116). A similar approach could be replicated for Community Driven Development (CDD) projects and local government and decentralized service delivery projects to achieve a multi-channel structure for third-party monitoring (offline, mobile, and web). The note documents the CivicTech pilot experience in Madagascar and lessons learned.